Second Double-Stranded RNA Binding Domain of Dicer-like Ribonuclease 1: Structural and Biochemical Characterization - Burdisso, Paula (2012)
Dicer-like ribonuclease III enzymes are involved in different paths related to RNA silencing in plants. Little is known about the structural aspects of these processes. Here we present a structural characterization of the second double-stranded RNA binding domain (dsRBD) of DCL1, which is presumed to participate in pri-micro-RNA recognition and subcellular localization of this protein. We determined the solution structure and found that it has a canonical fold but bears some variation with respect to other homologous domains. We also found that this domain binds both double-stranded RNA and double-stranded DNA, in contrast to most dsRBDs. Our characterization shows that this domain likely has functions other than substrate recognition and binding.